Etno cognitive properties range toponyms of Hindi and toponymy (Journal of Oriental Studies, 2018)
The anthropocentric position as one of the forms of Indian linguistic research conducted in the regional toponymy review of the system to a specific area – in the names of certain ethno-cultural regions, is the study of the relationship of spiritual history. Regional toponymic materials, show the distribution patterns inherent in all-Indian toponymy revealing linguistic history, ethnocultural, ethnoсognitive stories that are unique to this region.The article discusses lingvohistorical, ethnocultural, ethnoсognitive patterns characteristic of Indian toponymy.